Handedness and scale orientation effects on consumer usage of sensory scaling - Butterfield, Tyler (Kansas State University, 2021)
Sensory evaluation is integral to the understanding of individuals’ perceptions of products and how the creation of those goods meet their needs. Sensory scaling systems allow researchers to translate consumer perceptions into quantitative data that can more effectively relate the story of a product. However, in some cases, biases linked to the study or the participant can taint the validity of sensory studies, causing researchers to get the wrong message from consumers. This thesis evaluates whether participants of a consumer study have biases related to their handedness and the orientation of commonly used sensory scales. This research was comprised of three studies with varying products including breakfast sandwiches, sponges, and dry pet food requiring different senses to be engaged. Each of the individual studies utilized questions formatted in the 9-point hedonic, 5-point just-about-right, and 5-point expectation and purchase intent scales. Participants were placed in one of four groups based on their handedness, right or left, and the scale they received, standard or reversed, unbeknownst to them. The data was then analyzed using an analysis of variance test to determine if the differences between the four groups mean scores were significant (CI = 95%) and a chi-squared test to determine if the distribution of selection for right- and left-handed individuals was significant. The results showed that when individuals use a 9-point hedonic scale the orientation of the scale and the handedness of the individuals have little effect on the scores given. Across all the studies there were only three out of twenty-three attributes that displayed a significant difference between two of the groups. Interestingly, for the breakfast sandwich study and sponge study there was a consistent trend that left-handed participants rated products more highly when using the standard scale. Across all three studies, right-handed individuals rated products more highly when receiving the reversed scale. The results from the 5-point just-about-right questions were similar in that a few attribute mean scores were significantly different between the four groups, though no trend could be verified from the data. The chi-square test found few instances where the rate of liking was significantly different based on the scale orientation or handedness of the individuals. Overall, there is little effect of an individual’s handedness and the orientation on the scale on the responses by the consumer, yet the trend of how each handedness group scores based off the scale orientation which they are given should be further examined with larger sample sizes.
Keywords: Handedness; Scale orientation; Hedonic scaling; Sensory science; Consumer testing